Numerical investigation of the performance of bucket foundation installed in sand under vertical loading - Nabil Al Hakeem; Solomon Rubay; Charles Aubeny (Cogent Engineering, 2024)
Bucket foundations are circular surface foundations with thin skirts around the circumference. They have been successfully installed using economical suction or vibratory methods. Large-diameter buckets, up to 22 m, have been successfully deployed. In offshore wind power applications, bucket foundations are commonly configured in a tripod arrangement for fixed foundation wind turbines. While bucket foundations may be subjected to complex conditions of combined loading, this study presents an in-depth focus on a single loading mode: vertical compression. This study presents a finite element investigation of the performance and vertical load capacity of skirt foundations installed in the sand and subjected to vertical load passing through the bucket center. To take advantage of symmetry for problem geometry and applied load, an extensive parametric study was performed in this research utilizing an axisymmetric (two-dimensional) finite-element analysis employing the non-associated flow rule of the Mohr-Coulomb soil model. Comparisons to previously published 3D FE and experimental studies showed good agreement. The results showed that the pure vertical capacity of the bucket foundation significantly depends on skirt diameter D, aspect depth ratio (L/D), and relative density Dr. This research introduced simple design charts relating the vertical bearing capacity of skirted foundations to aspect ratio, diameter, and relative density.